Clinical and biochemical characteristics of people experiencing post-coronavirus disease 2019-related symptoms: A prospective follow-up investigation - Alfadda, Assim A.; Rafiullah, Mohamed; Alkhowaiter, Mohammad; Alotaibi, Naif; Alzahrani, Musa; Binkhamis, Khalifa; Siddiqui, Khalid; Youssef, Amira; Altalhi, Haifa; Almaghlouth, Ibrahim; Alarifi, Mohammed; Albanyan, Saleh; et al. (Frontiers in Medicine, 2022)
Background Post-acute coronavirus disease 2019 (COVID-19) syndrome, also known as long COVID, is a prolonged illness after the acute phase of COVID-19. Hospitalized patients were known to have persisting symptoms of fatigue, headache, dyspnea, and anosmia. There is a need to describe the characteristics of individuals with post-COVID-19 symptoms in comparison to the baseline characteristics. Purpose To investigate the clinical and biochemical characteristics of people who recovered from COVID-19 after 6 months of discharge from the hospital. Methods This was a prospective follow-up investigation of hospitalized and discharged COVID-19 patients. Adult patients admitted to King Saud University Medical City, Riyadh, Saudi Arabia, with laboratory-confirmed COVID-19 and discharged were recruited. The baseline demographic information, comorbidities, vital signs and symptoms, laboratory parameters, COVID-19 therapy, and outcomes were collected from the medical records. Blood samples were collected for cytokines estimation. A detailed interview about signs and symptoms was undertaken during the follow-up. Results Half of the followed-up people reported experiencing at least one of the COVID-19-related symptoms. The mean blood pressure was found higher in follow-up. People with the symptoms were characterized by low lymphocyte count, lower serum calcium levels, and hyperglycemia compared to people without any post-COVID-19 symptoms. Cytokines IL-8, VEGF, and MCP-1 were higher in people with the most frequent symptoms. Conclusion People with post-COVID-19 symptoms were characterized by lower lymphocyte count, lower serum calcium levels, and hyperglycemia compared to people without symptoms. Individuals with the most frequent post-COVID-19 symptoms had higher baseline pro-inflammatory, chemotactic, and angiogenic cytokines.